Active packaging: an alternative to minimum processed vegetables? (Research, Society and Development, 2022)
The demand for ready-to-eat fruits and vegetables is growing, with emphasis on the minimally processed vegetables (MPV) market. This increase is linked to the high nutritional value and the health benefits associated with the regular consumption of these foods. However, the damage caused by minimal processing to vegetables makes them more susceptible to spoilage. In this context, packaging, especially active packaging, plays an important role in preserving the sensory, nutritional and microbiological quality of these products. Thus, this review aimed to evaluate the effect of active packaging on MPV. Based on the studies described in the literature, it appears that the use of films and active coatings can act by minimizing the loss of moisture and the oxidation of different components (such as lipids and pigments), as well as delaying microbial deterioration, including restricting the growth of pathogenic microorganisms. These actions make it possible to prolong the shelf life of these foods. Therefore, active packaging technology has shown positive and promising results to maintain the quality, safety and sensory properties of these foods, however, there is a need to carry out more studies related to the cost and scalability of these materials applied in MPV.